Pengaruh Servant Leadership dan Komitmen Kerja terhadap Kinerja Pelayanan Pegawai Kecamatan Cibeunying Kaler Kota Bandung - Izni Alvira Oktaviani; Sri Suwarsi; Allya Roosallyn Assyofa (Bandung Conference Series: Business and Management, 2022)
Abstract. Service performance is an activity carried out by employees in providing the best and quality service to the community.. Servant leadership is needed by public institutions such as sub-district offices because in accordance with their vision and mission, public organizations as servants, especially stakeholders and leaders, can make community visits, attitudes, norms or values, opinions and so on. Commitment is seen as a value in the organization that shows that a person places great importance on his work and organization. This study uses a survey method. This type of causal associative research uses a descriptive and verification approach with quantitative data. The sample technique used a total sampling technique, namely the number of respondents as many as 32 employees. Research data collection techniques with surveys and interviews in the field as well as library research. The results of this study concluded that: 1) The leadership style of servant leadership in Cibeunying Kaler District was in a good category. 2) Employee work commitment in Cibeunying Kaler District was in a good category.3) Service performance of employees in Cibeunying Kaler District was in a good category. 4) Servant leadership affects service performance of employees in Cibeunying Kaler District 5) Work commitment affects employee service performance in Cibeunying Kaler District. 6) Servant leadership and work commitment affect service performance of employees in Cibeunying Kaler District. Abstrak. Kinerja pelayanan merupakan suatu aktivitas yang dilakukan oleh pegawai dalam memberikan pelayanan yang terbaik dan berkualitas kepada masyarakatServant leadership sangat dibutuhkan oleh lembaga publik seperti kantor kecamatan karena sesuai dengan visi dan misinya organisasi publik sebagai pelayan masyarakat khususnya stakeholder dan pemimpin dapat membuat visi, memperbaiki sikap, norma atau nilai-nilai dan perilaku, serta pendapat dan sebagainya. Komitmen dipandang sebagai nilai pada organisasi yang menunjukkan bahwa seseorang sangat mengutamakan pekerjaan dan organisasinya. Penelitian ini menggunakan metode survei. Jenis penelitian asosiatif kausal dengan menggunakan pendekatan deskriptif dan verifikatif dengan data kuantitatif. Teknik sampel menggunakan teknik total sampling yakni jumlah responden sebanyak 32 pegawai. Teknik pengumpulan data penelitian dengan survei dan wawancara ke lapangan serta penelitian kepustakaan. Hasil penelitian ini menyimpulkan bahwa:1)Gaya kepemimpinan servant leadership di Kecamatan Cibeunying Kaler Kota Bandung dalam kategori baik.2)Komitmen kerja pegawai Kecamatan Cibeunying Kaler dalam kategori baik.3)Kinerja pelayanan pegawai Kecamatan Cibeunying Kaler dalam kategori baik.4)Servant leadership mempengaruhi kinerja pelayanan pegawai Kecamatan Cibeunying Kaler 5)Komitmen kerja mempengaruhi kinerja pelayanan pegawai Kecamatan Cibeunying Kaler.6)Servant leadership dan komitmen kerja berpengaruh terhadap kinerja pelayanan pegawai Kecamatan Cibeunying Kaler.